manual   quickstart   instguide   update   basis

Next: C..7 B97DF: Density functional Up: C. Density functional descriptions Previous: C..5 B88C: Becke 1988   Contents   Index   PDF


C..6 B95: Becke 1995 Correlation Functional

$\tau$ dependent Dynamical correlation functional. \begin{dmath}
T=[ 0.031091, 0.015545, 0.016887]
,\end{dmath}

\begin{dmath}
U=[ 0.21370, 0.20548, 0.11125]
,\end{dmath}

\begin{dmath}
V=[ 7.5957, 14.1189, 10.357]
,\end{dmath}

\begin{dmath}
W=[ 3.5876, 6.1977, 3.6231]
,\end{dmath}

\begin{dmath}
X=[ 1.6382, 3.3662, 0.88026]
,\end{dmath}

\begin{dmath}
Y=[ 0.49294, 0.62517, 0.49671]
,\end{dmath}

\begin{dmath}
P=[1,1,1]
,\end{dmath}

\begin{dmath}
f={\frac {E}{1+l \left( \left( \chi \left( a \right) \right) ^{2}+
\left( \chi \left( b \right) \right) ^{2} \right) }}
,\end{dmath}

\begin{dmath}
g={\frac {F\epsilon \left( \rho \left( s \right) ,0 \right) }{H \left(
1+\nu\, \left( \chi \left( s \right) \right) ^{2} \right) ^{2}}}
,\end{dmath}

\begin{dmath}
G={\frac {F\epsilon \left( \rho \left( s \right) ,0 \right) }{H \left(
1+\nu\, \left( \chi \left( s \right) \right) ^{2} \right) ^{2}}}
,\end{dmath}

\begin{dmath}
E=\epsilon \left( \rho \left( a \right) ,\rho \left( b \right)
\r...
...ight) ,0 \right) -\epsilon
\left( \rho \left( b \right) ,0 \right)
,\end{dmath}

\begin{dmath}
l= 0.0031
,\end{dmath}

\begin{dmath}
F=\tau \left( s \right) -1/4\,{\frac {\sigma \left( {\it ss} \right) }{
\rho \left( s \right) }}
,\end{dmath}

\begin{dmath}
H=3/5\,{6}^{2/3} \left( {\pi }^{2} \right) ^{2/3} \left( \rho \left( s
\right) \right) ^{5/3}
,\end{dmath}

\begin{dmath}
\nu= 0.038
,\end{dmath}

\begin{dmath}
\epsilon \left( \alpha,\beta \right) = \left( \alpha+\beta \right)...
...ght) \left( \zeta \left( \alpha,\beta \right) \right) ^{
4} \right)
,\end{dmath}

\begin{dmath}
r \left( \alpha,\beta \right) =1/4\,\sqrt [3]{3}{4}^{2/3}\sqrt [3]{{
\frac {1}{\pi \, \left( \alpha+\beta \right) }}}
,\end{dmath}

\begin{dmath}
\zeta \left( \alpha,\beta \right) ={\frac {\alpha-\beta}{\alpha+\beta}}
,\end{dmath}

\begin{dmath}
\omega \left( z \right) ={\frac { \left( 1+z \right) ^{4/3}+ \left( 1-z
\right) ^{4/3}-2}{2\,\sqrt [3]{2}-2}}
,\end{dmath}

\begin{dmath}
e \left( r,t,u,v,w,x,y,p \right) =-2\,t \left( 1+ur \right) \ln
\...
...1}{t \left( v\sqrt {r}+wr+x{r}^{3/2}+y{r}^{p+1}
\right) }} \right)
,\end{dmath}

\begin{dmath}
c= 1.709921
.\end{dmath}



molpro@molpro.net 2018-01-19